A Model System for the Thermodynamic Analysis of Reaction‐Induced Phase Separation: Solutions of Polystyrene in Bifunctional Epoxy/Amine Monomers - Zucchi, Ileana Alicia (2004)
A model system, consisting of a linear polymer dissolved in a bifunctional monomer/co‐monomer solvent, was selected to test the applicability of the Flory‐Huggins (FH) theory in the absence of the usual assumptions present in the analysis of modified thermosetting polymers. Solutions of two almost monodisperse polystyrenes (PS, equation image = 83 000 or 217 000), in diglycidyl ether of bisphenol A (DGEBA) and in stoichiometric DGEBA/BA (benzylamine) solutions, exhibited an upper critical solution temperature (UCST) behavior. Cloud‐point curves (CPC) were fitted with the FH model using an interaction parameter depending on both temperature and concentration, χ = (a + b/T)/(1 − cϕ2), where ϕ2 represents the volume fraction of PS. A group‐contribution method provided a reasonable explanation of the observed trends. Cloud‐point times in the course of the DGEBA/BA stepwise polymerization, carried out at 70 °C and 80 °C, were determined for solutions containing 2.5 to 15 wt.‐% PS (equation image = 83 000). Times were transformed to conversions using kinetic curves determined by Fourier Transform Infrared Spectroscopy (FT‐IR) and Size Exclusion Chromatography (SEC). The analysis of cloud‐point conversions with the FH model was performed considering the (ideal) distribution of epoxy/amine species generated as a function of conversion. An empirical fitting of cloud‐point curves was possible with the use of an interaction parameter decreasing with conversion. Possibilities of improving the thermodynamic description of a polymerization‐induced phase separation are discussed.